2018
DOI: 10.1007/s00037-018-0172-8
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic tensor rank of graph tensors: beyond matrix multiplication

Abstract: We present an upper bound on the exponent of the asymptotic behaviour of the tensor rank of a family of tensors defined by the complete graph on k vertices. For k ≥ 4, we show that the exponent per edge is at most 0.77, outperforming the best known upper bound on the exponent per edge for matrix multiplication (k = 3), which is approximately 0.79. We raise the question whether for some k the exponent per edge can be below 2/3, i.e. can outperform matrix multiplication even if the matrix multiplication exponent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…The following theorem is our main technical result on which the rest of the paper rests. We note that for the tensor Kronecker product the statement is well-known in the context of algebraic complexity theory [6,7,16,17,8].…”
Section: Degeneration and Restrictionmentioning
confidence: 83%
See 2 more Smart Citations
“…The following theorem is our main technical result on which the rest of the paper rests. We note that for the tensor Kronecker product the statement is well-known in the context of algebraic complexity theory [6,7,16,17,8].…”
Section: Degeneration and Restrictionmentioning
confidence: 83%
“…In the language of graph tensors [8], Proposition 18 says that tensor rank is not multiplicative under taking disjoint unions of graphs.…”
Section: Tensor Rank Is Not Multiplicative Under the Tensor Productmentioning
confidence: 99%
See 1 more Smart Citation
“…, 0), etc. It is shown in [VC15] and [CVZ16], and independently in [HX15], that for all k ≥ 3 we have Q(D (1,k−1) ) = Q(Φ (1,k−1) ) = 2 h(k −1 ) , where h(p) denotes the binary entropy function. In [CVZ16] it is shown that Q(D (2,2) ) = Q(Φ (2,2) ) = 2 which in [AVZ] is extended to, for all even k ≥ 4, Q(D (k/2,k/2) ) = Q(Φ (k/2,k/2) ) = 2.…”
Section: Tight Tensorsmentioning
confidence: 99%
“…Namely, statement (29) becomes false when instead we let Φ ⊆ I 1 × · · · × I k with k ≥ 4 and we let the right-hand side of the equation be max P ∈P(Φ) min i 2 H(Pi) , see [CVZ16, Example 1.1.38]. In[CVZ16] the construction of Theorem 4.4 is extended to obtain a lower bound for Q(Φ) when k ≥ 4. This lower bound is not known to be tight in general.…”
mentioning
confidence: 99%